2020
DOI: 10.1016/j.ypmed.2019.105954
|View full text |Cite
|
Sign up to set email alerts
|

The effect of college attendance on young adult cigarette, e-cigarette, cigarillo, hookah and smokeless tobacco use and its potential for addressing tobacco-related health disparities

Abstract: The goal of this study was to assess the effect of college attendance on tobacco use among young adults and across subpopulations with disparities in tobacco use. Using a cohort of US youth (< 18 years) who aged into young adulthood (18-24 years) in the Population Assessment of Tobacco and Health (2013-14, 2015-16, n = 3619) and propensity score matching we estimated the effect of college attendance on past 30-day use of cigarettes, e-cigarettes, cigarillos, hookah and smokeless tobacco. In unmatched analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…A previous study of PATH waves 1–2 (2013–2015) estimating the association between perceptions of the harmfulness of hookah compared to cigarettes with initiation of ever hookah use at wave 2 found that those who perceive hookah as less harmful had increased odds of initiating hookah use (HR = 2.89; 95%CI = 1.82–4.61) compared to those who perceive hookah as more harmful than cigarettes [ 35 ]. Interestingly, recent studies suggest that most hookah users in college do not admit to their health care providers that they use hookah [ 36 ], potentially because of the infrequent use patterns of hookah products [ 37 ] and they incorrectly think that they are free from the risk of nicotine addiction [ 38 ]. Therefore, education and intervention campaigns are needed to correct misperceptions about the harmfulness and addictiveness of hookah among young adults, as our results show that many young adults initiate ever or past 30-day hookah users in this developmental stage of life.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of PATH waves 1–2 (2013–2015) estimating the association between perceptions of the harmfulness of hookah compared to cigarettes with initiation of ever hookah use at wave 2 found that those who perceive hookah as less harmful had increased odds of initiating hookah use (HR = 2.89; 95%CI = 1.82–4.61) compared to those who perceive hookah as more harmful than cigarettes [ 35 ]. Interestingly, recent studies suggest that most hookah users in college do not admit to their health care providers that they use hookah [ 36 ], potentially because of the infrequent use patterns of hookah products [ 37 ] and they incorrectly think that they are free from the risk of nicotine addiction [ 38 ]. Therefore, education and intervention campaigns are needed to correct misperceptions about the harmfulness and addictiveness of hookah among young adults, as our results show that many young adults initiate ever or past 30-day hookah users in this developmental stage of life.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Surgeon General reports, the majority of experimentation has ceased by age 25 but lifetime risks of tobacco-related diseases begin to increase. 1,7,39 Statistical analyses were conducted using SAS version 9.4. 40 All estimates were weighted using respondents' person-level TUS-CPS survey weights, and data were standardized by age and sex within race/ethnicity and educational categories to the 2010 US population.…”
Section: Methodsmentioning
confidence: 99%
“…Educational attainment has a major impact on smoking behaviors, where smoking rates generally decrease with increasing education levels. [4][5][6][7][8][9] An investigation of national cigarette smoking trends between 1974-1985 showed a large and increasing gap in smoking status across education, with an annual decline in smoking prevalence about five times greater among college graduates than those with less than a high school education. 10 The education gap in smoking rates continues to grow: in 2018, cigarette smoking rates were six times greater for US adults with less than a high school education than for those with an advanced degree.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco consumption impacts the entire system of the body with malignant long-lasting disorders [Mehrotra et al 2019;Azagba et al 2020;Leas et al 2020]. The relationship between the consumption of tobacco and disease has been extensively studied [Lachenmeier et al 2018].…”
Section: Tobacco Associated Disease Burdenmentioning
confidence: 99%